Rancang Bangun Prototipe Sistem Pemantauan dan Pemetaan Lampu Penerangan Jalan Umum (PJU) Berbasis Arduino UNO - Aleksander Bima Tansri; Mochamad Subianto; Romy Budhi Widodo; Yusuf Giovanno; Octaviani Intan Randi (SMATIKA JURNAL, 2020)
Public road lighting (PRL) is a facility used by the community to work at night. Dinas Perumahan dan Permukiman (DISPERKIM) department is a tasked with making improvements and regulating PRL. However, DISPERKIM officers are still experiencing delays in making PRL improvements, because PRL monitoring and regulation is still by visiting each PRL location. The experimental results show, the trial of sending data with 100 experimental from GSM Shield SIM900 gets 1.55 seconds, while the NRF24L01 device is 1.69 seconds. Based on the results of trials on sending data shows the delay of sending data for the prototype parent by 50.7 seconds, and 56.4 seconds. Whereas the testing delay of sending data for child prototypes was 147.8 seconds or 02:27 minutes, and by 143.5 seconds or 02:23 minutes. The function of experimental is helping officer (DISPERKIM) to get a data for calculation and prediction about PJU condition on every area. Based on the design of the test system can be stated to run well, because the system can do remote monitoring and mapping.